Changing demands made by senile dementia on the National Health Service. Issue 2 (June 1984) - Stilwell, J A; Hassall, C; Rose, S
Abstract : In 1976 and 1981 two studies were undertaken to identify the numbers of elderly severely mentally infirm patients receiving care in a range of institutions in Worcestershire and to examine the appropriateness of the special units planned for them. The numbers of planned places matched the totals of patients in care but the nature of the provision was wrong. The new units were planned for able bodied but demented patients, with a relatively low staff/patient ratio. The number of these patients had fallen by one third, being replaced by patients who needed heavy physical nursing care. The new units would not therefore be able to fulfil their planned role of providing cheaper care than did the geriatric or psychiatric hospitals.